Reframing Teacher Training Strategies for Legal and Human Rights Education: An Analytical Study on Strengthening National Civic Competence - Aprilio Poppy Belladonna; Yayuk Hidayah (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2026)
This study aimed to develop effective training strategies for teachers of Senior High Schools, Vocational Schools, and Islamic High Schools in strengthening education on Pancasila, human rights, law, and national insight to support the formation of a more just society. By implementing a Training of Trainers (ToT) approach, the study focused on enhancing teachers’ understanding and capacity not only to teach these values conceptually but also to integrate them meaningfully into their classroom practices. The research employed a qualitative method with a case study approach, involving teachers from Bandung and Cimahi who participated in the training program. The findings indicated that the training successfully improved teachers’ competencies in delivering theoretical and contextual learning related to Pancasila, human rights, law, and national insight in a more effective and engaging manner. Furthermore, the program encouraged teachers to internalize and transmit these values to students, fostering the development of individuals who possess legal awareness, respect for human rights, and active participation in national and civic life. The study also demonstrated that structured and reflective training activities can strengthen teachers’ pedagogical confidence and promote value-based learning environments in schools. Overall, this research contributes to the development of a teacher training model that emphasizes strengthening education on Pancasila, human rights, law, and national insight as fundamental pillars for cultivating responsible citizens and advancing the realization of a socially just society.